Gestational Hypoxia and Programing of Lung Metabolism - Rood, Kristiana; Lopez, Vanessa; La Frano, Michael R.; Fiehn, Oliver; Zhang, Lubo; Blood, Arlin B.; Wilson, Sean M. (Frontiers in Physiology, 2019)
Gestational hypoxia is a recognized risk factor in the development of pulmonary hypertension in the newborn and other sequela, however the mechanisms associated with disease remain poorly understood. This review highlights disruption of metabolism by antenatal high altitude hypoxia and the impact this has on pulmonary hypertension in the newborn with discussion of model organisms and human populations. There is particular emphasis on modifications in glucose and lipid metabolism along with alterations in mitochondrial function. Additional focus is placed on increases in oxidative stress and the progression of pulmonary vascular disease in the newborn and on the need for further exploration using a combination of contemporary and classical approaches.